2019
DOI: 10.1111/1541-4337.12439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postharvest Operations on Rice Grain Quality: A Review

Abstract: Postharvest operations, such as drying, storage, and milling, have been used to ameliorate the aging of rice grains and to achieve and maintain desirable rice grain quality, and thus play a key role in determining rice commercial quality and value. This review summarizes publications from the past decade and outlines the evidence supporting attribution of grain quality changes induced by postharvest processes to changes in the physical properties and chemical composition of the rice grain (starch, protein, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 112 publications
1
29
0
1
Order By: Relevance
“…In Kenya, approximately 10% of the grain is reported to be broken during milling [3]. Kernel breakage caused by poor postharvest handling of kernel and grains could increase infection and exacerbate fungal contamination [72].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, approximately 10% of the grain is reported to be broken during milling [3]. Kernel breakage caused by poor postharvest handling of kernel and grains could increase infection and exacerbate fungal contamination [72].…”
Section: Discussionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) grains stored for 6 months at 40 • C showed lower bound phenolic content and cooking time than grains stored at 16, 24 or 32 • C, although this depended on the cultivar [11]. When air becomes dry, caused by a high ratio of temperature to RH, rice grain quality is negatively impacted [12]. In a study on the influence of hyperbaric storage on bacterial (Bacillus subtilis) endospore growth in different matrices, RT was referred to as 'variable/uncontrolled' and defined as a wide range (16-24 • C) [13].…”
Section: Rt Fluctuation In Food Storage or Postharvest And Seed Germinationmentioning
confidence: 99%
“…The drying with average air temperature of 55° C and tempering of 240 min led to head rice yield (HRY) equivalent (p < 0.05) to that of the drying at average temperature of 30° C. Thus, it was observed that the higher the drying temperature employed, without proper tempering treatment, the greater the incidence of fissured grains and broken grains, and consequently, the lower the head rice yield (HRY). Rough rice grains subjected to drying temperatures above the glass transition temperature, without proper tempering treatment, do not resist high gradients of temperature and vapor pressure, which damage their physical integrity (TONG et al, 2019). Dong et al (2010) observed that after drying of rough rice (short grains), the tempering for 120 min eliminated about 80% of the moisture gradient created, which was an important factor in the formation of cracks and subsequent broken of grains.…”
Section: Fissures Head Rice Yield and Rice Whitenessmentioning
confidence: 99%